Factor Structure and Internal Consistency Reliability of the Croatian Version of the Family Adaptability and Cohesion Evaluation Scale (FACES) IV Package: A Preliminary Study - Gregorović Belaić, Zlatka; Čekolj, Nadja; Zloković, Jasminka (European Journal of Mental Health, 2024)
Introduction: A family operates as a dynamic system comprising various subsystems and is continually interacting with its environment. Therefore, it is essential to comprehend the underlying principles of family functioning. One of the most commonly used models for describing family functioning is the Circumplex Model of Marital and Family Systems (Olson & Gorall, 2003). Aims: In this study, we aimed at examining the factor structure and internal consistency reliability in the Croatian version of the Family Adaptability and Cohesion Evaluation Scale IV Package, which measures family functioning through family cohesion and flexibility at the balanced and unbalanced levels, as well as family communication and family satisfaction. Methods: Confirmatory factor analysis (CFA) and exploratory factor analysis (EFA) were performed using a convenient sample of 528 participants. Results: CFA revealed that the Croatian version of the FACES IV Package does not fit the theoretical model of the original factor structure in this preliminary study. The exceptions were the Family Communication Scale and Family Satisfaction Scale, which showed satisfactory parameters. The results of the EFA of FACES IV showed a 5-factor model solution. Conclusions: The Croatian version of the FACES IV Package is not completely suitable for use in the national context. Thus, given these preliminary findings, further testing on a more representative or clinical sample is recommended.